Soul Map Atlas: A Design-Science Framework Integrating Bazi, Numerology, Human Design, and Javanese Primbon with AI-Supported Self-Reflection in the Age of Digital Confession - Novia Angelina Zuraidy (Green Publisher Indonesia, 2026)
Individuals are increasingly disclosing emotional struggles to AI chatbots, yet current systems remain largely reactive and lack the narrative structure needed to support long-term identity clarity, particularly amid growing identity fragmentation in hyperconnected digital environments. In response to this gap, the present study aims to design and evaluate an AI-augmented, birth-based identity framework called Soul Map Atlas, which integrates BaZi, Numerology, Human Design, and Javanese Primbon with adaptive AI reflection to transform unstructured emotional disclosure into coherent, lifelong self-reflection. Following a Design Science Research approach, the study derives its design principles from a synthesis of identity theory, AI-mediated disclosure literature, and symbolic-system scholarship, articulates a Context–Agency–Mechanism–Outcome (CAMO) framework, and designs a three-module artefact consisting of Birth Essence, Symbolic Integration Engine, and AI Reflection Module. The prototype is evaluated qualitatively through a two- to three-week interaction phase followed by 30-minute interviews, with the resulting data analysed using thematic, cross-case, and convergence analysis. The findings show that participants experienced combining stable, culturally grounded symbolic anchors with psychologically safe, non-deterministic AI dialogue as supportive of interpretive resonance, emotional safety, and a stronger sense of narrative continuity, although birth-time uncertainty and the absence of expert review remain limitations of the study. Overall, Soul Map Atlas offers a new category of AI–symbolic reflective artefact with implications for life coaching, digital wellbeing tools, and culturally inclusive identity support, and it warrants further longitudinal and expert-reviewed evaluation.